PENINGKATAN KEPATUHAN PEMBAYARAN IURAN JAMINAN KESEHATAN NASIONAL MELALUI EDUKASI LITERASI FINANSIAL - Istyanto, Febry; Rahmi, Safirina Aulia (Institut Citra Internasional, 2025)
The National Health Insurance Program (JKN) by BPJS Kesehatan, as a pillar of Universal Health Coverage (UHC) in Indonesia, faces challenges in compliance with premium payments, particularly in the informal sector, necessitating an increase in financial literacy to ensure the sustainability of healthcare financing, especially regarding catastrophic illnesses. Therefore, improving compliance with JKN premium payments is essential, especially among informal workers. This community service activity will be conducted in areas with a high concentration of informal sector workers, such as online motorcycle taxi drivers and street vendors, over a two-month period in Sedayu, Bantul, Yogyakarta, in 2025, which includes preparation, education, and evaluation. The target of this activity is 40 informal workers registered as Independent Participants of BPJS Kesehatan from various backgrounds. Through an educational-participatory approach, this activity aims to enhance participants' awareness and ability to manage their finances as well as understand the importance of compliance with JKN premium payments. The results of this activity show an increase in the percentage of understanding regarding financial literacy and the importance of JKN premium payments. It can be concluded that financial literacy education positively impacts participants' compliance behavior